Dance-related injury - Motta-Valencia, K. (Physical Medicine & Rehabilitation Clinics of North America, 2006)
Although dance medicine has derived extensive knowledge from sports medicine, some aspects covered in the practice of dance medicine are unique to this field. Acute and overuse injuries must be analyzed within the scope of associated mechanisms of injury, mainly related to the practice of specific dance techniques. Even though most available medical literature concerning dance medicine is specific to ballet-related conditions, many of the concepts covered here and in other articles can be helpful in the treatment and diagnosis of participants in other dance disciplines. Continued research is expanding the knowledge on injury patterns of different dance disciplines. It is the experience of dance practitioners that dancers are quite in touch with their bodies; thus, when their ailments are systematically analyzed, and underlying cause can usually be identified. In this sense, it is evident that the principles of dance medicine and rehabilitation allow the practitioner to arrive at a diagnosis and treat the underlying causes to prevent reinjury, ameliorate sequelae from injury, and minimize residual deficits after injury.